Study of structural phase transition and elastic properties of ZnTe semiconducting compound under high pressure. (2022) - Karil, Poornima; Karma, Nikita; Dager, H.S.; Kaurav, Netram
Highlights: Zinc Telluride (ZnTe) semiconducting compound was studied by using the effective inter-ionic potential method. The structural phase transfer from B3 to B1 consists of estimated phase pressure values and abrupt volumetric changes in the pressures-volume phase diagram. The calculated results predict the transformation from B3 to B1 of ZnTe. Abstract: The high-pressure structural phase transition and pressure induced elastic properties of cubic zinc-blende phase ( B 3) to rock-salt phase ( B 1) structure of Zinc Telluride (ZnTe) semiconducting compound were studied by using the effective inter-ionic potential method, which contains the long-range Coulomb and van der Waals (vdW) interactions and the short-range repulsive interaction of up to second-neighbor ions within the Hafemeister and Flygare approach. The structural phase transition from B 3 to B 1 structure is reflected using estimated values of phase transition pressure and volumetric abrupt changes in the pressure–volume phase diagram. The calculated results first predict the phase transformation of ZnTe from B3 to B1, which occurs at 19GPa and is consistent with the reported data. Later on, using the effective inter-ionic potential technique, we were able to predict the second order elastic characteristics of the ZnTe system.